If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2g + -3(7g + 6) = -156 Reorder the terms: -2g + -3(6 + 7g) = -156 -2g + (6 * -3 + 7g * -3) = -156 -2g + (-18 + -21g) = -156 Reorder the terms: -18 + -2g + -21g = -156 Combine like terms: -2g + -21g = -23g -18 + -23g = -156 Solving -18 + -23g = -156 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -23g = -156 + 18 Combine like terms: -18 + 18 = 0 0 + -23g = -156 + 18 -23g = -156 + 18 Combine like terms: -156 + 18 = -138 -23g = -138 Divide each side by '-23'. g = 6 Simplifying g = 6
| 1k+9=6k-66 | | g(x)=-2x+13 | | 2=4/w | | -3(3b-2)= | | -5/5i | | 4/5y-20=160 | | 22x=23x-1 | | 8X=7X-21 | | 5-11=-3z | | 7(5x-4)-(5+7x)= | | 4r-p=q | | 12g=24 | | 9(6-5x)-2(3+6x)= | | 5(3x-2)=(2x-1) | | g(x)=3-9x | | 9(8+5m)= | | -8v+3(v+3)=14 | | 4(9x+8)-9(6-3x)= | | (x+4)(x+2)-3=0 | | (8x-4)+92=180 | | f(x)=x-17 | | 5(7x-8)-6(12x-4)= | | y=-9+5 | | 60+8x=80+6x | | 36x^2+16y^2+9z^2-144=0 | | 3z+5z-7z=7 | | 3/5x-7 | | 9(w+3)=3w+15 | | 6(3x-3)-(4+5x)= | | 2a-3=-5a+11 | | (fx)=2x-6 | | f(x)=x^2-10x+8 |